Online channels sales premia in times of COVID-19: First evidence from Germany - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2022)
Presence on the web tends to be important for firms. Empirical studies show that firms with a better performance along various dimensions, and firms that are more internationally active, tend to have a website. Furthermore, a website helped firms to survive in times of the COVID-19 pandemic. An open question that is not discussed in this literature is how the use of online channels for sales is related to various dimensions of firm performance. This note contributes to the literature by using a unique recently released set of firm level data from Germany to investigate for the first time the links between online channels sales and firm characteristics.
Keywords: D22; L25; 330; Online channels sales; firm performance; COVID-19; Germany 2021 Enterprise Survey Data Set